IDENTIFIKASI BERBAGAI JENIS HAMA PADI (Oriza Sativa) DI KECAMATAN NGRAYUN KABUPATEN PONOROGO SEBAGAI SUMBER BELAJAR SISWA SMP KELAS VIII SEMESTER GASAL POKOK BAHASAN HAMA DAN PENYAKIT - Suroto Suroto; R. Bekti Kiswardianta; Sri Utami (Jurnal Pendidikan, 2013)
Rice is the staple food of Indonesia's population . However, rice production in the country has not been able to meet the needs of the national rice . This research is descriptive qualitative exploration methods to make observations and identification of pests and pest morphological features of rice paddy field in the area of the District Ngrayun Ponorogo . Rice sampling technique was determined by cluster sampling method (sampling area) , pest sampling technique was determined by saturation sampling method for all members of the pest population is used as a sample . Based on research carried out on 15 samples of rice fields in the village of the District 10 Ngrayun obtained 10 kinds of pests of various species namely : Ladybug Green (Nezara viridula) , Ladybug limbed like leaves (Anasa tristis) , Walang Sangit (Leptocorica acuta) , Slant -faced Grasshopper (Chloealtis conspersa) , Protonum bertaji Grasshopper (Melanoplus sanguinipes) , White Moth (Tryporiza inotata), caterpillar Leaf Folder (Cnapalocrosis medinalis), green leafhoppers (Nephotettik nigropictus), grain Leaf Beetle (Oulena melanoplus) , Colorado Potato Beetle (Leptinotarsa decemlineata) , and Insect Aft Body Tail Spring (Onychiurus ramous).